2021
DOI: 10.1021/acs.jctc.1c00637
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Accuracy of Water Models through the Van Hove Correlation Function

Abstract: We present molecular-simulation-based calculations of the Van Hove correlation function (VHF) of water using multiple modeling approaches: classical molecular dynamics with simple three-site nonpolarizable models, with a polarizable model, and with a reactive force field; density functional tight-binding molecular dynamics; and ab initio molecular dynamics. Due to the many orders of magnitude difference in the computational cost of these approaches, we investigate how small and short the simulations can be whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…The rst 100 ps of the trajectory was used for equilibration, and the remaining 1.5 ns of the run was used for analysis, where MD trajectory snapshots were collected every 10 fs. We note that, based on the simulations with different system sizes (1000, 512, 250 and 128 water molecules) for bulk water, Matsumoto et al 44 found that no signicant system size effects are introduced in the smaller systems, and that 128 water molecules are sufficient to study the VHF and its peak behaviors with time. Also, the typical system size used in the study of aqueous ions with AIMD-based simulations is less than or equal to 128 molecules, with the length of the simulation within a few hundred ps.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…The rst 100 ps of the trajectory was used for equilibration, and the remaining 1.5 ns of the run was used for analysis, where MD trajectory snapshots were collected every 10 fs. We note that, based on the simulations with different system sizes (1000, 512, 250 and 128 water molecules) for bulk water, Matsumoto et al 44 found that no signicant system size effects are introduced in the smaller systems, and that 128 water molecules are sufficient to study the VHF and its peak behaviors with time. Also, the typical system size used in the study of aqueous ions with AIMD-based simulations is less than or equal to 128 molecules, with the length of the simulation within a few hundred ps.…”
Section: Methodsmentioning
confidence: 83%
“…The rst peak of the pure water VHF at t ¼ 0 is at z2.8 Å and the second peak is at z4.5 Å, consistent with the static PDF of pure water. As time elapses, the rst peak position moves towards higher values of r and the second peak position moves towards lower values of r. 44 As discussed above for the static PDFs, the addition of ions can signcantly inuence the water VHF and even introduce distinct new spectral features. Unless otherwise noted, we focus on a salt concentration of 1.2 mol kg À1 molality for clarity, and is sufficient to illustrate the important effects of the salt ions on the water VHF.…”
Section: Validation Of the Dftb/md Methodologymentioning
confidence: 86%
See 3 more Smart Citations